Influence of Use of Social Media of Government Agencies on Trust to the Government: Study on Social Media Owned by Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi DKI Jakarta - Marpianta, Dina Anggia; Hendriyani, Hendriyani (JURNAL KOMUNIKASI INDONESIA, 2019)
This research examines the influence of social media usage in government agencies toward trust in the government. This study focuses on the social media owned by the Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi DKI Jakarta [the Office of Investment and One Stop-Intergrated-Services]; namely Instagram, Twitter, and Facebook account @layananja-karta. This is a quantitative survey that takes a sample from followers of those social media accounts, conducting in Jakarta byasking the respondent to fill out an online questionnaire. PLS Structural Equation Modelling (SEM) is used to analyse obtained data, to test and estimate relationships with the integration of factor analysis and path analysis. This study finds that using social media could increase trust toward the government as long as the public perceives transparency and interactivity in social media communication.